Application of Smartwatches in Elderly Care with Indoor Localization Functionality - Arvai, Laszlo (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The recent achievements in mobile technology and wearable OS makes possible to create comfortably wearable and very capable smartwatches. They have many different sensors and powerful hardware combined with general purpose OS and all this available for reasonable price. It makes it ideal device for elderly care. Monitoring the elderly’s basic health condition is very straightforward, but using smartwatch as an indoor localization device, monitoring the motion activity, recognizing the typical motion patterns of wandering is not simple. Even those watches are really capable devices, they are not equipped with direct indoor localization sensors and we would like to avoid installing special equipment’s, markers, transmitters in the home of elderly. Using only a commercially available smartwatch hardware for indoor localization is a challenging task, several filtering and data processing algorithms needs to be combined in order to provide acceptable indoor localization function. The algorithms, their connection and fine-tuning methods are explained in this article.